Case Report: Challenging Perioperative Decision-Making in a Neonate With Transposition of Great Arteries and Novel Coronary Anatomy - Chegondi, Madhuradhar; Ricci, Marco; Ashwath, Ravi C. (Frontiers in Pediatrics, 2022)
Transposition of great arteries (d-TGA) is often associated with various coronary artery (CA) patterns. These anomalous patterns can cause variable clinical symptoms of coronary ischemia including sudden death. CA pattern is one of the major determinants of outcome in TGA postoperatively. Advanced cardiac imaging and a multidisciplinary care approach are essential for a favorable outcome. Herein we describe a novel CA origin pattern in a neonate with d-TGA, who developed myocardial ischemia and required coronary unroofing procedure for full recovery.